Enhanced precision of low-temperature quantum thermometry via dynamical control - Zwick, Analía Elizabeth (2019)
Precise probing of quantum systems is one of the keys to progress in diverse quantum technologies, includingquantum metrology, quantum information processing and quantum many-body manipulations. We consider athermometer modelled by a dynamically-controlled multilevel quantum system in contact with a thermal bath.As opposed to the diverging relative error near absolute zero of previously suggested thermometers, dynamicalcontrol of the probe enables high-precision thermometry close to the absolute zero, with a constant (temperature-independent) relative error bound, by maximizing its quantum Fisher information. The proposed approach may finddiverse applications related to precise probing of the temperatures of many-body quantum systems in condensedmatter and ultracold gases, as well as in different branches of quantum metrology beyond thermometry, forexample in precise probing of different Hamiltonian parameters in many-body quantum critical systems.